2005
DOI: 10.1001/archinte.165.8.936
|View full text |Cite
|
Sign up to set email alerts
|

Renal Outcomes in High-Risk Hypertensive Patients Treated With an Angiotensin-Converting Enzyme Inhibitor or a Calcium Channel Blocker vs a Diuretic

Abstract: In hypertensive patients with reduced GFR, neither amlodipine nor lisinopril was superior to chlorthalidone in reducing the rate of development of ESRD or a 50% or greater decrement in GFR. Participants assigned to receive amlodipine had a higher GFR than those assigned to receive chlorthalidone, but rates of development of ESRD were not different between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(74 citation statements)
references
References 36 publications
(20 reference statements)
3
69
0
2
Order By: Relevance
“…Hydrochlorothiazide (HCT) is cheap antihypertensive drug proven to be effective in hypertension. 17 However, a study done in six low and middle income countries including Nepal observed that the median availability of HCT varied from 0 to 10%, 8 which is also reflected in our study. Unavailability of this cheap and effective medicine has two consequences.…”
Section: Medicine To Treat Ncds Constitute Minor Portion Ofsupporting
confidence: 50%
“…Hydrochlorothiazide (HCT) is cheap antihypertensive drug proven to be effective in hypertension. 17 However, a study done in six low and middle income countries including Nepal observed that the median availability of HCT varied from 0 to 10%, 8 which is also reflected in our study. Unavailability of this cheap and effective medicine has two consequences.…”
Section: Medicine To Treat Ncds Constitute Minor Portion Ofsupporting
confidence: 50%
“…Thus, it is likely that the baseline CVD risk in AASK was lower than in high-risk populations without these exclusions. 6,8,15 Still, in participants with self-report of previous CVD, the rate of ESRD exceeded the rate of CVD mortality.…”
Section: ͻ0001mentioning
confidence: 94%
“…3,8-10, 37,44 In hypertensive diabetic patients with macroalbuminuria and renal insufficiency, ACE inhibitors and ARBs slow progression to end-stage renal disease (ESRD) by ~ 25% compared to other antihypertensive agents; this renoprotective effect may be lost or muted as renal failure progresses and serum creatinine rises to > 3.0 mg/dl. 3 An abrupt decline in renal function or a significant increase in serum potassium may occur in patients with renal insufficiency treated with these agents, and frequent monitoring (1-2 weeks) of electrolytes and renal function is recommended after the initiation or upward titration of these drugs.…”
Section: Pharmacological Treatment Of Hypertension In Diabetesmentioning
confidence: 99%